Community Behavior Patterns That Influence The Causes of Dengue Hemorrhagic Fever (DHF) in The Pondok Petir Elementary Region - Aulia Saputra (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the bite of the Aedes Aegypti mosquito infected with one of the four types of dengue virus with clinical manifestations of fever, muscle aches, and/or joint pain accompanied by leukopenia, rash, lymphadenopathy, thrombocytopenia and hemorrhagic diathesis. In dengue hemorrhagic fever, plasma leakage occurs which is characterized by hemoconcentration (increased hematocrit) or fluid accumulation in body cavities (World Health Organization). Dengue Hemorrhagic Fever Penyakit (DHF) is still one of the main public health problems in Indonesia. The number of sufferers and the area of ​​spread of DHF is increasing along with the increase in mobility and population density, especially in tropical and sub-tropical areas (Kemenkes RI, 2010). At the beginning of 2019, Dengue Hemorrhagic Fever (DHF) again increased in several areas, even becoming an Extraordinary Event (KLB) status. In January 2019 there were 15,132 DHF sufferers with 145 people dying in 34 provinces. This figure is twice as high as the figure at the end of January 2018 which recorded 6,167 DHF sufferers with 43 people dying. To find out the behavioral factors of DHF disease in the community in the Pondok Petir sub-district area in 2020. Research Setting: According to data in 2019, Dengue Hemorrhagic Fever (DHF) has increased again in several areas, even becoming an Extraordinary Event (KLB) status. In January 2019 there were 15,132 DHF sufferers with 145 people dying in 34 provinces. This figure is twice as high as the figure at the end of January 2018 which recorded 6,167 DHF sufferers with 43 people dying. East Java, West Java, and DKI Jakarta are the three provinces that experienced an increase in the number of dengue cases compared to the previous year. This research uses the Simple Random Sampling technique. This study studied the incidence of dengue in children to adults (dependent variable), with respondent characteristics (age, history of dengue disease), counseling (knowledge), attitudes (family attitudes), and behavioral patterns (behavior of health workers, rarely monitoring larvae). mosquitoes, distribution of abate powder, fogging activities), and increasing community participation in dengue prevention (independent variable). To obtain the data, an in-depth interview and document review approach was conducted with the community at Pondok Petir. This research was conducted at Pondok Petir, South Tangerang in June 2021. The sub-categories in this study were DHF, Age, History of DHF, Knowledge, Family Attitude, Behavioral Patterns, Behavioral Patterns of Health Workers, Rarely Monitoring Mosquito Larvae, Distribution of Abate Powder, Fogging Activities, Facilities, Facilities, Increased Participation Society in Dengue Prevention. It takes a lot of education to the people of Pondok Petir to make people aware of the importance of knowing about DHF. The most effective and efficient prevention of dengue fever to date is the Mosquito Nest Eradication (PSN) activity using 3M Plus, namely: 1) Draining, is cleaning places that are often used as water reservoirs such as bathtubs, water buckets, water reservoirs drinking water, water reservoirs, refrigerators, etc. 2) Closing, namely closing water reservoirs such as drums, jugs, water towers, and so on; and 3) Reusing or recycling used goods that have the potential to become breeding grounds for dengue-transmitting mosquitoes.